Fra køn til diversitet – intersektionalitet i en dansk/nordisk kontekst - Ann-Dorte Christensen (The Royal Danish Library, 2006)
Intersectionality is a travelling concept rooted in Black Feminism that has recently been adopted by Nordic gender research. The concept has been transformed on its way from the US to the Danish/Nordic context. The purpose with this article is to contribute to a critical reflection of the concept and discuss its potentials from a Danish/Nordic context. Adopting a social science optic we first discuss some tensions between the original American understanding of the concept and the special – predominantly poststructural and postcolonial  conceptualisation given in the Danish/ Nordic context. Secondly we present two analytical frames able to analyse the dynamic interaction between different forms of power and between structures, institutions and identities. We argue that  intersectionality is not a coherent theory but a new perspective able to contain different and competing theoretical and methodological approaches.